Resesi dan Dampaknya Terhadap Perekonomian Indonesia - Effendi, Bahtiar; Pangestuti, Nabila Kurnia (BanKu: Jurnal Perbankan dan Keuangan, 2024)
Indonesia as an open economy has the opportunity to be affected by the dynamics in the global financial market. As in 2008, where Indonesia was affected by the financial crisis that began in the United States and several other countries which then became a global economic crisis. The type of research used in this research is literature review. The data collection technique in this study was carried out using the documentation method. Therefore, in this research, the data source uses secondary data. Secondary data is obtained from books, journals, documents, or other reference sources related to the topic of the problem discussed. From this data, it will then be analyzed using descriptive analysis in order to know about the potential for recession and its impact on the Indonesian economy, especially Islamic banks and MSMEs. In facing problems related to the recession, several Islamic banks have prepared several steps and strategies, namely strengthening third party funds (DPK), encouraging the growth of low-cost funds or CASA (Current Account Savings Account), and Islamic banks have focused only on the retail segment. Furthermore, namely the increase in financing carried out by Islamic banks in helping to deal with the decline in economic growth and the closure of several MSMEs in Indonesia after Covid-19. In Islamic banks, financing expenditures that often have an impact on banking conditions are financing expenditures that cause non-performing loans (NPF). Steps that can be taken to overcome the impact of the recession, namely, diversifying destination countries in export activities. While in the investment sector, Indonesia needs to increase investment.